Development of rhizoremediation as a treatment technology in the removal of Polycyclic aromatic Hydrocarbons (PAHs) from the environment - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2007.